Estrategias metodológicas y el desarrollo de destrezas con criterio de desempeño en el bloque “soy ciudadana o ciudadano” del área de estudios sociales en los niños y niñas del cuarto año del subnivel básica media, de educación general básica de la escuela Julio Matovelle” de la ciudad de Loja, año lectivo 2013 - 2014 - González Japón, Dolores Fernanda (2016)
This research titled METHODOLOGICAL STRATEGIES AND DEVELOPMENT OF SKILLS WITH STANDARD PERFORMANCE IN BLOCK "I AM CITIZEN OR CITIZEN" AREA OF SOCIAL STUDIES IN CHILDREN OF FOURTH GRADE sublevel BASIC MEDIA GENERAL BASIC EDUCATION SCHOOL "JULY Matovelle" LOJA CITY, SCHOOL YEAR 2013 - 2014. the overall objective is to contribute to the improvement of skills development with performance criterion on the block "I am a citizen or citizen" of the Department of Social Studies in children and fourth grade girls General Education Basic school "Julio Matovelle" city of Loja. The study was qualitative, the methods used were scientific, descriptive, analytic-synthetic, statistical, deductive; Likewise survey techniques were applied through the instrument of the questionnaire aimed at two teachers and 40 students in the fourth grade of elementary school. For the development of research work surveys conducted were applied to teachers and students of the educational unit to meet the methodological strategies used in the teachinglearning skill development, then we proceeded to perform the analysis and interpretation of results the same which served for the respective conclusions and recommendations. Among the main findings of the research process it was determined that teachers use methodological strategies as rain, ideas, cartographic material and plenary; however the students expressed that teachers make use of the text as a learning also became known that students have learned to be passive, to follow rules of adults and assimilate responsibilities with the block I 'm single citizen. By the results it is concluded that teachers use traditional methodological strategies , and scarcely make use of educational models for teaching and learning process ; teachers are recommended didactic teaching strategies to develop skills with performance criterion on the block "I am a citizen or citizen" of the Department of Social Studies.